Demand Response Driven Load Scheduling in Formal Smart Grid Framework - Azar, Armin Ghasem (Technical Report Electronics and Computer Engineering, 2016)
In this technical report, we present the current state of the research conducted during the first part of the PhD project named “Demand Response Driven Load Scheduling in Formal Smart Grid Framework”. The PhD project focuses on smart grids which employ information and communication technologies to assist the electricity production, distribution, and consumption. Designing smart grid applications is a novel challenging task that requires modeling, integrating, and validating different grid aspects in an efficient way. The project tackles such challenges by proposing an effective framework to formally describe smart grid elements along with their interactions. To validate this framework, the report concentrates on deploying efficiency in managing the electricity consumption in households which requires focusing on different impacts of demand response programs running in the smart grid to engage consumers to participate. A demand response system is considered which is connected to all households and utilizes their information to determine an effective load management strategy taking into account the grid constraints imposed by distribution system operators. The main responsibility of the demand response system is scheduling the operation of appliances of a large number of consumers in order to achieve a network-wide optimized performance. Finally, the PhD report demonstrates the simulation results, publications, courses, and dissemination activities done during this period. They are followed by envisaging future plans that will lead to completion of the PhD study.